Methods for volume inference of non-medical objects from images: A short review - Nabitchita, Baticté; Gonçalves, Norberto Jorge; Coelho, Paulo Jorge; Pimenta, Luís; Zdravevski, Eftim; Lameski, Petre; Costa, Mónica; Neves, Paulo Alexandre; Pires, Ivan Miguel (SAGE Publications, 2024)
Nowadays, the object’s volume is essential for monitoring any scene. Technological equipment is evolving, and mobile devices and other devices embed high-resolution cameras. The high-resolution cameras open a window for different research studies, where the volume measurement is vital for different areas. This study aims to identify image processing techniques for measuring the object’s volume. Thus, a systematic review was performed with a Natural Language Processing (NLP)-based framework for identifying studies between 2010 and 2023 related to the measurement of object volume. As a result of this search, this paper reviewed and analyzed 25 studies, verifying that different computer vision methods accurately handle object recognition. Additionally, an evaluation of the databases presented by the studies above is performed to consider further the design of a new approach to infer the volume of objects from an image.